PROMOSI APLIKASI “SAYURBABA” TERHADAP KEPUTUSAN PEMBELIAN MELALUI MEDIA DIGITAL DI PONTIANAK - Wiani, Putri Maylita (Jurnal Social Economic of Agriculture, 2019)
Nowadays many emerging businesses use digital media accounts to advertise their products, therefore the competition in business becomes tougher. Businessman should pay attention to promotional components through digital media in accordance with their target market to make the message provided effective, efficient and meet the intended use.The purposes is to structure the promotion of application sayurbaba on purchasing decisions trough digital media in Pontianak city. Survey method with 100 respondents by purposive sampling. Data collected through online questionnaires via google form. The analysis using Structural Equation Modeling through LISREL 8.80 software. The results proved that promotion of application Sayurbaba on purchasing decisions trough digital media in Pontianak city was composed of collaboration and connection components which were measured by sharing posts, customer testimonials, useful content and promotions.Keywords: Context,Communication,Collaboration, Connection, SEM